Scientific Considerations on the Grammar of Turkish Adjectives - Axmedjanova Dilafruz Batirovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, information is given about the inclusion of scientific researches that have been carried out for many years. It should be noted that Turkic root words are a linguistic fact that shows the origin, formation, and development of Turkic languages, and illuminates the historical and life experience of the people who communicate in this language remains an issue.